Application of ARIMA Methods on Unemployment and Inflation Rates in Nigeria - Akobi, Clement; Ogunmola, Adeniyi (Asian Journal of Science, Technology, Engineering, and Art, 2024)
In Nigeria, Unemployment and inflation rate are some of the problems bedeviling the economy. The inability of Job seekers to secure gainful employment tends to create disaffection among these people and cause some of them especially the youth, to resort to social vices. In the motivation to experience low unemployment rate and inflation rate which are economic indicators in Nigeria, deriving appropriate ARIMA model to give insight into future occurrence of these indicators for intervention calls for the application of ARIMA model. This study seek to fit ARIMA model to unemployment rate and inflation rate and forecast future values for both unemployment rate and inflation rate. Utilizing secondary data sourced from the National Bureau of Statistics (NBS) from 1991 to 2020. The findings reveal that, for each of the two series, to obtain the appropriate ARIMA model that fits the data, ten closely suitable ARIMA models were identified. Using the least values of AIC, AICc and BIC as selection criteria, ARIMA (0, 1, 1) was found to be the best fitted model for each of the two series. Subsequent diagnostic checks confirm the adequacy of the fitted models, with residual analyses indicating no significant autocorrelation or heteroscedasticity. The forecasted values for the unemployment rate series and inflation rate series maintain a constant point forecast. This implies that unemployment rate and inflation rate in Nigeria does not reveal a noticeable increase nor decrease but will be constant in Nigeria. Due to the unchanging forecasted value which appears not to be decreasing, there is need for interventions that will lead to the visible reduction of present unemployment rate and inflation rate in Nigeria.